2019
DOI: 10.1088/1748-0221/14/02/c02008
|View full text |Cite
|
Sign up to set email alerts
|

X-ray investigation on the Superconducting Source for Ions (SuSI)

Abstract: Heavy ion facilities such as the National Superconducting Cyclotron Laboratory (NSCL) often use ECR Ion Sources (ECRIS) for the production of highly charged ions to increase the efficiency of accelerating structures. Axial bremsstrahlung emission was studied on the Superconducting Source for Ions (SuSI) at the NSCL for 18 GHz and 13 GHz operation with oxygen. The hot electron temperatures were estimated from the bremsstrahlung high energy tail and seem to depend only on magnetic minimum in the same way as was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…This means that the present diagnostics is unable to reveal oscillating behavior with significant variations of plasma parameters with resolution lower than the ms. Different independent measurements [13,14,29,30] have shown that the same threshold value found in this paper plays a key role in establishing the conditions for Cyclotron-Maser instabilities. A future paper will discuss about time-resolved measurements able to show temporal evolution of plasma parameters in sub-ms temporal domain.…”
Section: Discussionsupporting
confidence: 70%
“…This means that the present diagnostics is unable to reveal oscillating behavior with significant variations of plasma parameters with resolution lower than the ms. Different independent measurements [13,14,29,30] have shown that the same threshold value found in this paper plays a key role in establishing the conditions for Cyclotron-Maser instabilities. A future paper will discuss about time-resolved measurements able to show temporal evolution of plasma parameters in sub-ms temporal domain.…”
Section: Discussionsupporting
confidence: 70%
“…The highest value of the magnetic field will be in correspondence of the injection and/or extraction axial coils inner surface, so during the numerical design of the magnetic system one has to be careful at not exceeding the threshold field values relative to the magnet material. In superconducting traps, special attention must be paid to the minimum field, B min , that should be tuneable within a wide range of values: it has been experimental observed that, in order to obtain the highest electron density and to reach the optimal charge state, one has to have 0.65 < B min /B ECR < 0.75 Benitez et al [5]; Mazzaglia et al [6]; Neben et al [7]. If this ratio exceeds the upper value, sudden non linear effects arise, increasing the plasma x-ray emission and thus the heat load on the cryostat.…”
Section: Ecr Ion Sources Magnetic Systemmentioning
confidence: 99%
“…X-ray plasma diagnostics for ECR (Electron Cyclotron Resonance) ion sources and traps have been developed along the years allowing volumetric characterization of the plasma [5][6][7][8][9][10][11]. At INFN-LNS several non invasive plasma diagnostic tools have been developed [12], with advanced analytical methods [13].…”
Section: Introductionmentioning
confidence: 99%